PENGUKURAN KINERJA PEMBANGKIT LISTRIK TENAGA BIOGAS BERBASIS LIMBAH CAIR PABRIK KELAPA SAWIT - Kiki Utama Putra; Zahrul Ulum; Aminah Asmara Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract. A crucial indicator of biogas power plant performance is the quality of the biogas entering the gas engine. Poor-quality biogas causes issues such as startup failures, corrosion of intercooler fins, and scoring of pistons and cylinders, in addition to reducing oil lifespan. Therefore, this study aims to detect performance degradation in the biogas power plant by measuring its operational performance using Key Performance Indicators (KPIs). The performance measurement process revealed declines in specific areas, namely the digestion KPIs regarding inlet pH and inlet temperature; this was attributed to the absence of a cooling pond system and a mixing pit at the plant. Regarding biogas condition KPIs, H2S and O2 levels were found to be suboptimal. However, gas engine consumption metrics were within acceptable limits, with consumption below 2 kWh/m³ and a Capacity Factor (CF) of 45%. Based on these measurements, optimization of the biogas system is required, as H2S and O2 levels did not meet KPI standards. The study concludes that KPIs can serve as a valuable reference for assessing and integrating the performance of biogas power plants.